(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Little information is available comparing wheat forage varieties, rumen fermentation and biomass production for different wheat (Triticum aestivum L.) cultivars. A combination of grazing and in vitro experiments was conducted at Texas A & M (TAM) AgriLife Research and Extension Center, Vernon, TX from 2003 to 2004. Our objective was to determine the effects of wheat varieties (WV) and forage allowances (FA) on in vitro rumen fermentation rate, forage biomass production, time of sampling, and grain yields under grazing by steers. The 2003 experiment consisted of 14 commercial wheat cultivars (a part of the UVT collection) and was a part of the TAM Wheat Breeding Program statewide evaluation test. Hereford steers (Bos tuurus L.; 220 to 233 kg) were grazed from November 2003 to May 2004. Grain yield was measured in May 2004. Across WV, total forage protein and soluble protein content were declined from February to March 2004. Total forage protein contents were higher for HG-9, Thunderbolt and Maton Rye than for Lockett, Cutter, Jagalene and Triticale in March. In vitro dry matter (DM) digestibility (IVDMD) was greater (P<0.01) for Maton Rye than for other WV. Forage DM production varied between FA (P<001), grazing (P<0.001), and WV (P<0.001), with no FA x WV and FA x WV x grazing interactions. Total forage DM production was greater (P<0.001) for Gagalene, Longhoern, TAM 111, TAM Bar 501, Lockett, Marton rye, and Jagalene than for HG-9, Triticale 5019, and Triticale 6331 WV in high-FA during grazing, but DM production in un-grazed plot was higher for Triticale 5019, TAM Bar 501 and Jagalene than for HG-9 and Ogallala varieties during the end of March. Across FA, forage DM production (kg DM/ha) in high-FA was higher (P<0.001) DM production than low-FA. Potential in vitro rumen DM disappearance rate (a+b; %) was not differences among WV and time of sampling date, but instantly solubilized rate (a) in the rumen was higher (P<0.05) for Maton rye and Cutter in February and Triticale, Maton rye and Jagalene in March 17 than for other WV, which lead to differentiation of high soluble carbohydrate among forage WV. Similar to rumen DM disappearance rate, instantly NDF solubilized rate (a: %) in the rumen were higher (P<0.05) for Triticale, Maton rye and Jagalene in March 17 than for other WV, suggests that higher rate of instantly solubilized of DM, rate of disappearance rate, and instantly solubilized NDF in the rumen may lead to initiating trigger factor for frothy bloat and need to further study. When steers grazing on high-FA, grain yields were greater (P<0.01) for 2174, Lockett, Thurnderbolt, TAM 111, and HG-9 than for low-FA, with Gagalene and Cutter being produced higher (P<0.01) grain yield than other WV. The pull of date (POD) response to grain yield depends upon the time of date with no or variable responses of grain yield with increasing time of date up to March 08. When POD after March 08 or thereafter, grain yield progressively decreased with time. Therefore, beneficial effects of POD for dual purpose winter wheat occur in the range from February 19 to March 08.